A balanced formula of essential amino acids promotes brain mitochondrial biogenesis and protects neurons from ischemic insult - Ragni, Maurizio; Fenaroli, Francesca; Ruocco, Chiara; Segala, Agnese; D’Antona, Giuseppe; Nisoli, Enzo; Valerio, Alessandra (Frontiers in Neuroscience, 2023)
Mitochondrial dysfunction plays a key role in the aging process, and aging is a strong risk factor for neurodegenerative diseases or brain injury characterized by impairment of mitochondrial function. Among these, ischemic stroke is one of the leading causes of death and permanent disability worldwide. Pharmacological approaches for its prevention and therapy are limited. Although non-pharmacological interventions such as physical exercise, which promotes brain mitochondrial biogenesis, have been shown to exert preventive effects against ischemic stroke, regular feasibility is complex in older people, and nutraceutical strategies could be valuable alternatives. We show here that dietary supplementation with a balanced essential amino acid mixture (BCAAem) increased mitochondrial biogenesis and the endogenous antioxidant response in the hippocampus of middle-aged mice to an extent comparable to those elicited by treadmill exercise training, suggesting BCAAem as an effective exercise mimetic on brain mitochondrial health and disease prevention. In vitro BCAAem treatment directly exerted mitochondrial biogenic effects and induced antioxidant enzyme expression in primary mouse cortical neurons. Further, exposure to BCAAem protected cortical neurons from the ischemic damage induced by an in vitro model of cerebral ischemia (oxygen-glucose deprivation, OGD). BCAAem-mediated protection against OGD was abolished in the presence of rapamycin, Torin-1, or L-NAME, indicating the requirement of both mTOR and eNOS signaling pathways in the BCAAem effects. We propose BCAAem supplementation as an alternative to physical exercise to prevent brain mitochondrial derangements leading to neurodegeneration and as a nutraceutical intervention aiding recovery after cerebral ischemia in conjunction with conventional drugs.